Incidence and survival of haemophagocytic lymphohistiocytosis: A population‐based cohort study from England. (22nd December 2021) - West, Joe; Card, Tim R.; Bishton, Mark J.; Lanyon, Peter; Ban, Lu; Bythell, Mary; Elliss‐Brookes, Lucy; Manson, Jessica J.; Nanduri, Vasanta; Rankin, Judith; Tattersall, Rachel S.; Crooks, Colin J.
Abstract: Background: Haemophagocytic lymphohistiocytosis (HLH) is a rare hyper‐inflammatory condition with poor outcomes. Objectives: Few population‐based estimates of the incidence and survival in adults exist. We aimed to provide these data for England. Methods: We used population‐based linked data from primary care, secondary care, cancer registries and mortality databases in England to identify people diagnosed with HLH between 1 January 2000 and 31 December 2016. We calculated annual incidence rates by age and sex, modelled change in incidence over time with Poisson regression, calculated overall 1‐year survival using Kaplan–Meier methods and estimated adjusted hazard ratios (HRs) of death using a Cox proportional hazards model. Results: We identified 214 patients with HLH. The reported age and sex‐adjusted incidence increased twofold over the period, from around one to around two per million. Incidence was highest in those below 1 year (14.6 per million) and ≥75 years (2.2 per million), and lowest in those aged 15–44 years (0.8 per million). One‐year survival varied by age and sex from 77% (95% confidence interval [CI] 63%–86%) in those <15 years to 30% (95% CI 14%–49%) in those ≥75. In patients with haematological cancer, the adjusted HR for death was 2.60 (95% CI 1.45–4.66) compared to patients with no malignant or rheumatological disease. Conclusion: The incidence of HLH diagnosis in England has increased between 2000 and 2016 and occurs in all ages with varying underlying diseases. One‐year survival varies substantially, being particularly poor in those aged over 75 years and those with haematological malignancy. Abstract :